2021
DOI: 10.1038/s41467-021-22231-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phase seismic source imprint of tropical cyclones

Abstract: The coupling between the ocean activity driven by winds and the solid Earth generates seismic signals recorded by seismometers worldwide. The 2–10 s period band, known as secondary microseism, represents the largest background seismic wavefield. While moving over the ocean, tropical cyclones generate particularly strong and localized sources of secondary microseisms that are detected remotely by seismic arrays. We assess and compare the seismic sources of P, SV, and SH waves associated with typhoon Ioke (2006)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Gualtieri et al (2018) suggested an adaptative statistical model, which demonstrated the relationship between the spectral amplitude of the short-period secondary microseism and the tropical cyclone intensity in the northwest Pacific Ocean. In addition to background noise, the body waves or multi-phase seismic sources were also found to be associated with cyclones, and it was successfully demonstrated by a few researchers (Gualtieri et al, 2018;Retailleau & Gualtieri, 2021). It is now believed that the seismological tools could be better used to track the path of the cyclone juxtaposed oceanic wave models with several limitations, including a resolution that is found to be too coarse for tropical cyclones producing aliasing, underdetermining the wind speeds and oceanic wave heights, and computing facilities etc (Chi et al, 2010;Fan et al, 2019;Retailleau & Gualtieri, 2019;Sufri et al, 2014;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…Gualtieri et al (2018) suggested an adaptative statistical model, which demonstrated the relationship between the spectral amplitude of the short-period secondary microseism and the tropical cyclone intensity in the northwest Pacific Ocean. In addition to background noise, the body waves or multi-phase seismic sources were also found to be associated with cyclones, and it was successfully demonstrated by a few researchers (Gualtieri et al, 2018;Retailleau & Gualtieri, 2021). It is now believed that the seismological tools could be better used to track the path of the cyclone juxtaposed oceanic wave models with several limitations, including a resolution that is found to be too coarse for tropical cyclones producing aliasing, underdetermining the wind speeds and oceanic wave heights, and computing facilities etc (Chi et al, 2010;Fan et al, 2019;Retailleau & Gualtieri, 2019;Sufri et al, 2014;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 87%
“…The energy bands from 0.05 to 0.10 Hz are clearly recognized in the spectrograms. PSD analysis as single-frequency microseism bands, or primary energy from Oceanic waves (Hasselmann, 1963), and 0.10-0.50 Hz energy spectrum is considered secondary microseisms (Cessaro, 1994;Longuet-Higgins, 1950;Retailleau & Gualtieri, 2021). Bromirski et al (2005) further classified double-frequency microseism as short-period (0.20-0.45 Hz) double-frequency and long-period (0.085-0.2 Hz) double-frequency energy bands.…”
Section: Earth and Space Sciencementioning
confidence: 99%
See 2 more Smart Citations
“…Ocean microseisms are generally divided into primary (PM), having the same frequency as the causative SGW and being generated often close to the shore, and secondary microseisms (SM), with twice the frequency of the forcing SGW. Teleseismic observations of both, deep‐ and shallow‐water microseisms exist (e.g., Beucler et al., 2015; Kedar et al., 2008; Landès et al., 2010; Traer et al., 2012; Ying et al., 2014) and the theoretical understanding of the ocean‐seafloor‐subsurface coupling has been developed since early works (e.g., Longuet‐Higgins, 1950, 1953) up to more recent advances (e.g., Ardhuin et al., 2011; Retailleau & Gualtieri, 2021). However, a detailed knowledge on the localization of the cyclone‐related microseismic sources, as well as their shape, spectral characteristics and their exact relation with the physical properties of the generating cyclones is still in development.…”
Section: Introductionmentioning
confidence: 99%